Competencies of Peruvian primary care nurses in the control of growth and development in the infant population - Aliaga-Sánchez, Ruth América (2024)
Objective. To measure the level of competency development of Peruvian primary care nurses in the control of growth and development of children under five years old. Methods. A cross-sectional, descriptive, quantitative study was designed with a population group of 100 nurses working in primary care health networks located in Lima, Ica, and Trujillo, using a non-probabilistic census sampling method. Data were collected using observation as the technique; the instrument was a performance checklist for growth, development, and immunizations. Results. The majority of the studied nurses presented a low level of competencies related to the growth and development of Peruvian children under five years old (60%), while 37% presented a medium level of performance in these competencies, and only 3% demonstrated a high level. Conclusions. Peruvian primary care pediatric nurses present low levels of competencies in the control of growth and development in children.